Konsep Wiku Ideal Dalam Kidung Cowak - Ida Bagus Heri Juniawan; Ida Bagus Alit Arta Wiguna (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This text contains many values of sublime teachings that must be used as guidelines by sulinggih candidates or sulinggih in carrying out swadharma to serve the community, especially in the spiritual field. Before serving the people, a sulinggih must prepare himself thoroughly and master sadhana, sesana, wariga, yoga, brata and jñana. The mastery of this knowledge will greatly determine the ideal quality as a sulinggih who is used as a role model and protector of humanity. This study aims to reduce the text, describe the content of the text and translate it freely into Indonesian. For people who do not know how to read and write Balinese script, it will be easier to understand. In addition, this research reveals the concept of the ideal wiku including, Right Purpose, Choosing a Teacher, Yoga, Putusing Aji. To achieve this goal, the method used is the method of Data Collection, Data Analysis, Presentation of Research Results. This research is a literature research with the object of study of Kidung Cowak manuscripts that researchers found from the storage of private collections of the Lombok community. There are several considerations for researchers to reveal this Kidung Cowak manuscript as follows: (1) Kidung Cowak manuscripts are not well known in the community. (2) To the best of the researcher's knowledge, the manuscript of Kidung Cowak has not been studied philologically. (3) Kidung Cowak manuscript contains many teachings about sublimity which are still relevant as a reference and guideline for sulinggih candidates and those who have become sulinggih.